Pengembangan Media Pembelajaran Audio-visual Bermuatan Literasi Sains Menggunakan Aplikasi Powtoon tentang Materi Keanekaragaman Hayati: Development of Audio-visual Learning Media Containing Science Literacy Using the Powtoon Application on Biodiversity Materials - Khafiza Sania; Relsas Yogica; Ristiono Ristiono; Ganda Hijah Selaras (BIODIK, 2022)
Scientific literacy is related to the ability of students to understand the process of the occurrence of science. In order to make it easier for students to improve scientific literacy skills, a media in learning is needed. Powtoon is an interesting application that can improve students' scientific literacy skills. The purpose of this research is to produce audio-visual learning media containing scientific literacy using the Powtoon application on biodiversity material for class X high school students. This research is research and development with the Instructional Development Institute (IDI) model. The research subjects were two lecturers from the Biology department, FMIPA UNP, one Biology teacher at the UNP Laboratory Development High School, and 32 students from class X MIA 1 SMA UNP Laboratory Development. The data obtained in this study are in the form of validity and practicality data. This research produces an Audio-visual Learning Media with Science Literacy Using Powtoon Application on Biodiversity Materials that is valid and practical. Key words: Science Literacy, Powtoon, IDI Â  Abstrak. Literasi sains berkaitan dengan kemampuan peserta didik dalam memahami proses terjadinya ilmu pengetahuan. Agar memudahkan peserta didik dalam meningkatkan kemampuan literasi sains diperlukan sebuah media dalam pembalajaran. Powtoon merupakan aplikasi menarik yang dapat meningkatkan kemampuan literasi sains peserta didik. Tujuan dari penelitian ini adalah menghasilkan media pembelajaran audio-visual bermuatan literasi sains menggunakan aplikasi powtoonÂ  tentang materi keanekaragaman hayati untuk peserta didik kelas X SMA. Penelitian ini adalah penelitian pengembangan (Research and Development) dengan model Instructional Development Institute (IDI). Subjek penelitian adalah dua orang dosen dari jurusan Biologi FMIPA UNP, satu orang guru Biologi SMA Pembangunan Laboratorium UNP, dan 32 orang peserta didik kelas X MIA 1 SMA Pembangunan Laboratorium UNP. Data yang didapatkan dalam penelitian ini berupa data validitas dan praktikalitas. Penelitian ini menghasilkan Media Pembelajaran Audio-visual Bermuatan Literasi Sains Menggunakan Aplikasi Powtoon tentang Materi Keanekaragaman Hayati yang valid dan praktis. Kata kunci: Literasi Sains, Powtoon, IDI